Bahatska O. V. Concept balance in the narrative structure of the modern Аmerican stories - Bahatska O. V. (Philological Treatises, 2020)
The article deals with the textual embodiment of the concept BALANCE, which is reflected in the three consequent stages of its realization in the fiction stories analyzed: the initial balance of the characters, its upsetting and recovery. These stages predetermine the narrative structure of the modern American stories by means of the characters’ conflict with social/physical environment, with one another (outer conflicts) or with themselves (inner conflicts) manifestation.